Acciones de daños por infracciones al derecho de la competencia en Colombia - De la Calle Restrepo, José Miguel (2024)
The purpose of competition law is to preserve economic competition; however, anticompetitive practices impact the market, affecting consumers and entrepreneurs. Despite this, the Colombian competition authority, the Superintendence of Industry and Commerce (hereinafter, "SIC"), cannot resolve disputes between private parties, as the legal framework of competition law was designed to protect a public good. Thus, the process to claim damages caused by anticompetitive practices follows the standard procedure of civil liability, making it difficult for affected parties to seek redress.This text analyzes actions for damages in Colombian competition law, comparing them with regional legislation and developments in Europe and the United States. Concrete proposals are offered to strengthen the role of competition law in protecting business interests and in denouncing those who cause harm as a means to preserve economic competition.